Alzheimerpårørende i møte med omgivelsene : En autoetnografisk studie - Lyngsnes, Kitt Margaret (Nordisk Tidsskrift for Helseforskning, 2022)
More than 100,000 people in Norway are living with dementia. A few of them have been diagnosed before the age of 65 and are thus in the category "early onset dementia". The aim of the study presented in this article is to explore one aspect of being a caregiver when one’s spouse has received an Alzheimer’s diagnosis at a young age. The article throws light on being next of kin in a situation characterized by care and grief and at the same time dealing with the questions and input from the outside world regarding the partner’s dementia. The research approach is autoethnographic, and the empirical material consists of experiences drawn from a period over several years. A key finding of the study is the importance of reflecting on one’s experiences both alone and with others. Furthermore, the connection between one’s subjective experiences and the dominant «dementia narrative» in our culture is highlighted.